Etiopathogenic theories of nervous system diseases in Vilnius in the early 19th century: “insanity and epilepsy exacerbate when the moonlight shines” - Sakalauskaitė-Juodeikienė, E. (Neurologijos seminarai, 2023)
Neurology as a separate branch of clinical medicine was not yet formed in Europe in the early 19th century. However, in the medical writings of the Vilnius University (VU) authors of that time, the brain was already called the “noblest organ of the human body”, the seat of the soul, the centre of external senses, and the primary beginning of all bodily movements. The aim of the present study is to reveal various etiopathogenic theories of diseases of the nervous system (NS) in Vilnius region, since this knowledge may indicate that there were some beginnings of clinical neurology in the early 19th century in Vilnius. First, we analysed old doctoral dissertations on NS diseases defended at VU in 1803-1832; we then turned to Consessus Caesareae Societatis Medicae Vilnensis (The Protocols of Vilnius Medical Society) and analysed clinical reports recorded in 1806-1842. Our study revealed that although humoralism was the most popular system of medicine, the main causes of NS diseases were believed to be in the solid parts of the human body (influence of solidism theory). It was also assumed that some NS diseases may be inherited or caused by fetal diseases in utero. On the other hand, one of the oldest theories, imaginatio gravidarum, was still prevalent in Vilnius at the time. It was also stated that some NS diseases may be triggered by physical and mechanical causes, concomitant diseases, medications and drinks, strong emotions, or violation of sleep hygiene. “Inflammatory agents” were reported to cause traumatic tetanus as inflammation spread upwards from the nerve endings, tendons, and ligaments to the brain. The authors also described the theory of “poison, specifically acting on the NS” that was transmitted by a rabid animal to a bitten patient. To describe the etiopathogenesis of spinal cord diseases, the concept of “diminishing vital spirits through the loss of bodily matter” was used (it was claimed, e.g., that excessive number of sexual intercourses dried out the spinal cord). In addition, the astrological causes of NS diseases were also believed to be of great importance (“somnambulism, insanity, and epilepsy exacerbate when the moonlight shines”). Finally, cutting off the Polish plait (plica polonica) was considered to be an essential etiological factor of various NS diseases in Vilnius in the early 19th century.
Keywords: nervous system diseases; etiopathogenesis; Vilnius University; Vilnius Clinics; nineteenth century